A registry review of 2532 catheter ablations for atrial fibrillation using active thermal protection. (24th May 2021) - Leung, L; Bajpai, A; Zuberi, Z; Li, A; Norman, M; Kaba, RA; Sohal, M; Akhtar, Z; Evranos, B; Gonna, H; Harding, I; Al Subaie, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Dr Leung has received research support from Attune Medical (Chicago, IL). Dr Gallagher has received research funding from Attune Medical (Chicago, IL). Background:   Thermal injury to the oesophagus causes a spectrum of adverse effects after ablation for atrial fibrillation (AF); at the most severe end, atrio-oesophageal fistula carries a high mortality rate. Controlled active thermal protection in the oesophagus during ablation is the most promising method of oesophageal protection. Randomized evidence from the IMPACT trial (NCT03819946) showed an 83.4% reduction in endoscopically detected oesophageal lesions compared to standard care when an oesophageal temperature control device was used to control the local temperature. The IMPACT patients who were randomized to the use of the device had no adverse event related to its use.  Real world registry data on applications of this device have not previously been available.  Purpose: To determine the safety of an oesophageal temperature control device by review of real-world registry data on its clinical use and any reported device-related adverse events. Methods:   We reviewed the following databases for any reported oesophageal temperature control device-related complications: The United States Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE), FDA Medical and Radiation Emitting Device Recalls, the Medicines and Healthcare products Regulatory Agency (MHRA) Medical Device Alerts and SwissMedic records of Field Safety Corrective Actions (FSCA). An internal registry (post-marketing follow up) database maintained by the manufacturer of the device was used to quantify the number used for each indication.  Reported events were reviewed and catalogued for description and identification of any events related to its use in the cardiac electrophysiology lab. The IMPACT study patients were reviewed for any device-related events. Results:   Of the 13, 284 oesophageal temperature control devices used, 2532 were recorded as having been used for the purpose of oesophageal protection during catheter ablation for AF.  A total of 5 events associated with the device were identified, all from the MAUDE database.  Three were from 2017, one from 2018, and one from 2019.  All involved its use in critical care or trauma patients and were related to user error or contraindicated patient selection; none resulted in serious harm to the patient. No adverse events occurred related to its use in the cardiac electrophysiology lab. No case of clinically significant oesophageal injury was reported in a patient who had been protected by the oesophageal temperature control device. Conclusions: Real world registry data has shown no adverse events reported to date in over 2500 uses of an oesophageal temperature control device in the cardiac electrophysiology lab, for the purpose of active thermal protection. This data supports the randomized trial evidence of its clinical effectiveness.